Transformation between Australian datums using a modified transverse Mercator projection - Featherstone, Will; Galloway, D.; Goulding, P.; Reit, B. (Mapping Sciences Institute Australia, 1999)
The introduction of the Geocentric Datum of Australia (GDA94) in the year 2000 will undoubtedly require the transformation of a large amount of coordinate data in Australia. This paper presents a modified transverse Mercator (MTM) map-projection such that the latitude and longitude on one datum are projected so that they closely agree with the transverse Mercator easting and northing on another datum. This approach will allow the introduction of the GDA94 whilst preserving Australian Map Grid (AMG) coordinates. Conversely, the MTM projection can be used to transform coordinates directly from the Australian Geodetic Datum (AGD) to the new Map Grid of Australia (MGA94). In order to test these two approaches, MTM parameters have been computed from 82 co-located GDA94/MGA94 and AGD98/AMG84 coordinates that comprise the Western Australian STATEFIX geodetic network. When using the national seven- and three-parameter datum transformations, the maximum differences between observed and transformed coordinates are 2.04m and 2.21m, respectively. When using the transformation by MTM projection, the projected coordinates agree with the observed coordinates to less than 2.04m.